Karakteristik Pasien Hidrosefalus di RSUD Ulin Banjarmasin Tahun 2018-2020 - Muhammad Ananda Putera; Agus Suhendar; Fakhrurrazy Fakhrurrazy; Ardik Lahdimawan; Istiana Istiana (Homeostasis, 2022)
Abstract: Hydrocephalus is a disorder or disease caused by increased intracranial pressure which is characterized by an increase in cerebrospinal fluid, caused by tumors, congenital, vascular disorders, infections, and head injuries. Hydrocephalus can cause seizures, neurological deficits, headache, fever, and paralysis, which causes a decrease in quality of life. This study aims to determine the characteristics of hydrocephalus patients at Ulin Hospital Banjarmasin in 2018-2020. This type of research is a descriptive retrospective research. The highest number of hydrocephalus cases was in 2018 namely 143 patients (49.14%). The 46 - 55 years old age group is the most patient age group. Males were found the most among hydrocephalus patients. The majority of patients came from South Kalimantan. Islam is the religion of most of the patients. The majority of patients are BPJS participants. Family history was found in 81 patients (29.56%) and a history of allergies was found in 19 patients (6.52%). Patients with headache and loss of consciousness are the majority of clinical symptoms in patients. Vascular abnormalities, tumors, and congenital are the most common causes in patients. Communicating hydrocephalus is the most common classification. The category of GCS scores in and out of patients that are often encountered is GCS 13-15. The majority of patients' length of stay was 15 days. The majority of patients improved after undergoing treatment. So, it can be concluded that most of them were in 2018, Islam, South Kalimantan, BPJS participants, male, with headache, 46-55 years old, communicating hydrocephalus, with GCS 13-15, length of treatment 15 days, and improving. Keywords: Characteristics, Hydrocephalus  Abstrak: Hidrosefalus adalah suatu kelainan atau penyakit yang disebabkan oleh peningkatan tekanan intrakranial yang ditandai dengan adanya peningkatan cairan serebrospinal, yang disebabkan oleh tumor, kongenital, kelainan vaskular, infeksi, dan cedera kepala. Hidrosefalus dapat menimbulkan kejang, defisit neurologis, nyeri kepala, demam dan paralisis yang menyebabkan penurunan kualitas hidup. Penelitian ini bertujuan untuk mengetahui karakteristik pasien hidrosefalus di RSUD Ulin Banjarmasin tahun 2018-2020. Jenis penelitian ini adalah deskriptif retrospektif. Jumlah kasus hidrosefalus paling banyak terdapat pada tahun 2018 yaitu 143 pasien (49,14%). Kelompok usia 46-55 tahun merupakan kelompok usia pasien terbanyak. Laki-laki ditemukan paling banyak diantara pasien hidrosefalus. Mayoritas pasien berasal dari Kalimantan Selatan. Islam merupakan agama terbanyak dari pasien. Mayoritas pasien adalah peserta BPJS. Ditemukan riwayat keluarga pada 81 pasien (29,56%) dan untuk riwayat alergi ditemukan pada 19 pasien (6,52%). Pasien dengan nyeri kepala dan penurunan kesadaran merupakan gejala klinis mayoritas pada pasien. Kelainan vaskular, tumor, dan kongenital merupakan penyebab paling banyak pada pasien. Hidrosefalus komunikans merupakan klasifikasi terbanyak. Kategori skor GCS masuk dan keluar pasien yang sering ditemui adalah GCS 13-15. Mayoritas Lama perawatan pasien adalah ≥15 hari. Mayoritas pasien membaik setelah menjalani pengobatan. Maka dapat disimpulkan paling banyak terdapat pada tahun 2018, islam, Kalimantan Selatan, peserta BPJS, laki-laki, dengan nyeri kepala, usia 46-55 tahun, hidrosefalus komunikans, dengan GCS 13-15, lama perawatan 15 hari, dan membaik. Kata-kata Kunci: Karakteristik, hidrosefalus